An Imaginary Trio King Solomon, Jesus, and Aristotle - Shavit, Yaacov (De Gruyter, 2020)
This book focuses on places and instances where Solomon's legendary biography intersects with those of Jesus Christ and of Aristotle. Solomon is the axis around which this trio revolves, the thread that binds it together. It is based on the premise that there exists a correspondence, both overt and implied, between these three biographies, that has taken shape within a vast, multifaceted field of texts for more than two thousand years.